2011
DOI: 10.1111/j.1365-2672.2011.05009.x
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and genetic stability of hybrids of industrial wine yeasts Saccharomyces sensu stricto complex

Abstract: Aims:  The aim of this study was to examine the physiological and genetic stability of hybrids of industrial wine yeasts Saccharomyces sensu stricto complex subjected to acidic stress during fermentation. Methods and Results:  Laboratory‐constructed yeast hybrids, one intraspecific Saccharomyces cerevisiae × S. cerevisiae and three interspecific S. cerevisiae ×Saccharomyces bayanus, were subcultured in aerobic or anaerobic conditions in media with or without l‐malic acid. Changes in the biochemical profiles, k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 55 publications
2
27
0
Order By: Relevance
“…the genomes of interspecific hybrids originating from the same parents can stabilize differently, resulting in different genomic configurations, as reported in previous studies targeting interspecific hybrids (30,32,44,45). Newly developed interspecific hybrids show a broad temperature tolerance range.…”
Section: Figmentioning
confidence: 52%
See 1 more Smart Citation
“…the genomes of interspecific hybrids originating from the same parents can stabilize differently, resulting in different genomic configurations, as reported in previous studies targeting interspecific hybrids (30,32,44,45). Newly developed interspecific hybrids show a broad temperature tolerance range.…”
Section: Figmentioning
confidence: 52%
“…Previous research showed that newly formed interspecific hybrid genomes are characterized by high plasticity and that genome rearrangements, such as whole or partial chromosome losses and introgressions, are common and can be directed by the environmental stress conditions applied (30,31,44,45). For example Dunn and coworkers (30) showed that newly formed interspecific hybrids between S. cerevisiae and S. uvarum exhibited a characteristic genome rearrangement pattern when hybrids were grown under continuous ammonium limitations (30).…”
Section: Figmentioning
confidence: 99%
“…This method has been applied successfully to produce a variety of interspecific hybrids between Saccharomyces sensu stricto species (see Table S2 in the supplemental material) in order to study speciation, epistasis, genetic compatibility, and stability of hybrid genomes (70,192) or simply to produce new strains with novel physiological properties (5,13,99,193). Mass mating was also applied successfully to produce hybrids between more distantly related yeasts (131).…”
Section: Interspecific Matingmentioning
confidence: 99%
“…The classical genetic and molecular methods applied, such as sporulation and crosses, karyotyping, AFLP analysis, DNA-DNA hybridization, and the partial sequencing of a few selected genes, were not sufficient to fully characterize the hybrid genomes. These methods were sufficient, however, to indicate that hybrid lines generally undergo progressive genome stabilization, during which large genomic rearrangements occur, including aneuploidization, chromosomal translocation, and partial or total chromosome loss (6,42,90,99,123,174,175,198). Gene amplification also occurs, especially in subtelomeric regions of chromosomes.…”
Section: Evolution Of Hybrid Genomesmentioning
confidence: 99%
“…uvarum were crossed, and the natural hybrids were obtained. The hybrids were able to decompose up to 77% of malic acid present in musts [23]. In another study, Redzepovic et al [24] worked with Saccharomyces paradoxus yeast strain isolated from Croatian grapes, as with S. bayanus and S. cerevisiae (Lalvin and Lallemand-France).…”
Section: General Introductionmentioning
confidence: 99%